Maternal Spiritual Coping Scale: Development and Validation - (:unkn) unknown (My University, 2018)
This research intends to develop a spiritual coping strategies scale for childrearing mothers. The study has been conducted using 24 itemsand has been carried out on 217 mothers. As a result of factor analysis, items have been categorized under one factor, and the total explainedvariance has been found to be approximately 0.59. As a result of the study, Cronbach’s alpha coefficient for the scale has been found as .966. Itemanalysis indicates the item-total correlation to be significant (p < .001). All these results show that all items have the same structure. The upperand lower values of the item-total correlations range from .630 to .838. The relationship of the scores from the Religious Coping Scale with thosefrom the Maternal Spiritual Coping Scale has been used for criterion validity. Statistically significant and positive correlations have been foundbetween the subscales of the Maternal Spiritual Coping Scale and Religious Coping Scale; the sub-scales of positive coping (r = .72; p = .01) andnegative coping (r = .35; p = .01) have been determined to significantly correlate. The results of the study show the scale to be a sufficiently validand reliable measurement tool that can be used to assess the coping strategies mothers use while raising children.

Bu araştırma, çocuk yetiştirmede anneler için manevi baş etme stratejilerini ölçmek amacıyla ölçek geliştirmeyi hedeflemiştir. Çalışma 24 maddeyle yürütülmüş olup ve toplamda 217 anneye ulaşılmıştır. Faktör analizi sonucunda öğeler bir faktör olarak kategorize edilmiş ve açıklanan toplam varyans yaklaşık 0.59 olarak bulunmuştur. Çalışma sonucunda ölçeğin Cronbach alfa katsayısı .966’dır. Madde analizi, madde toplam korelasyonunun anlamlı olduğunu göstermektedir (p <.001). Tüm bu sonuçlar, tüm öğelerin aynı yapı içinde olduğunu göstermektedir. Madde toplam korelasyonlarının alt ve üst değerleri, .630 ile .838 aralığındadır. Kriter geçerliği için kullanılan Dini Başa Çıkma Ölçeği ile Anne Manevi Başa Çıkma Ölçeği skorları arasındaki ilişki ise anlamlı bir ilişkidir. Anne Manevi Başa Çıkma Ölçeği ile Dini Başa Çıkma Ölçeği, Pozitif Başa Çıkma (r = .72; p = .01) ve Olumsuz Başa Çıkma (r = .35; p = .01) arasında istatistiksel olarak anlamlı pozitif korelasyonlar olduğu belirlenmiştir. Araştırmanın sonuçları, annelerin çocukları yetiştirirken kullandıkları baş etme stratejilerini değerlendirmek için kullanılabilecek yeterince geçerli ve güvenilir bir ölçme aracı olduğunu göstermektedir.
Anne Manevi Başa Çıkma Ölçeği: Geliştirme ve Geçerlik Çalışması
Keywords: Psikoloji